2007
DOI: 10.1155/2008/845651
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship in Acute Care Centres: A Survey of 68 Hospitals in Quebec

Abstract: Over one-quarter of Quebec hospitals do not have an ASP, and few hospitals in Quebec are currently evaluating their use of antimicrobials on a quantitative basis. In some cases, the lack of a QASP may be due to the allocation of insufficient pharmaceutical resources to antimicrobial stewardship (ie, less than one full-time pharmacist).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…This rate now has increased to 73%. Our findings are consistent with other published reports, which have ranged from 55% of general hospitals in 2001 15 to 74% in 2006 16 and again in 2008, 17 and 51% of pediatric hospitals in 2009. 18 Guidelines recommend that ASPs should be customized to adapt to local antimicrobial use and resistance patterns and to accommodate institutional needs and resources.…”
Section: Support For Antimicrobial Stewardship Programssupporting
confidence: 94%
“…This rate now has increased to 73%. Our findings are consistent with other published reports, which have ranged from 55% of general hospitals in 2001 15 to 74% in 2006 16 and again in 2008, 17 and 51% of pediatric hospitals in 2009. 18 Guidelines recommend that ASPs should be customized to adapt to local antimicrobial use and resistance patterns and to accommodate institutional needs and resources.…”
Section: Support For Antimicrobial Stewardship Programssupporting
confidence: 94%
“…In the province of Quebec (Canada), a survey of 68 hospitals in 2008 found that clinical microbiologists participated in 89% of antimicrobial stewardship surveillance programs (59). In this province, as in some other countries, most microbiologists are also trained and certified as ID specialists.…”
Section: Drugmentioning
confidence: 99%
“…This figure is good also when compared with countries well organised in this setting, such as Canada, where a study identified that 22% of the hospitals in Quebec published such reports regularly [15].…”
Section: Discussionmentioning
confidence: 78%
“…In conclusion, as the presence ASPs is increasing throughout the world, this survey shows that a multimodal approach, to date the best strategy available, has been implemented in all PHTs of Emilia-Romagna [4,15]. The results of a survey like the one performed here may represent an instrument to favour a better allocation of resources, both at the peripheral and central level.…”
Section: Discussionmentioning
confidence: 79%